(untitled) (Scientia Agricola, 2018)
Rootstocks influence certain characteristics of the scion, such as vigor, fruit yield and quality, and tolerance to biotic and abiotic factors. In conventional citrus breeding programs, hybridization is the main method used for obtaining rootstock varieties. Between Sept and Oct 2006, controlled pollinations were carried out resulting in nine progenies, totaling 461 hybrid seedlings. The female parents were the ‘Santa Cruz Rangpur’ lime (SCRL) and the ‘Sunki of Florida’ mandarin (SFM), while the male parents, in addition to this mandarin, were the ‘Indio’ and ‘Riverside’ citrandarins, the ‘Thomasville’ citrangequat (THOM), the ‘Swingle’ citrumelo, the ‘Argentina’ citrange (AGC) and the ‘Benecke’ trifoliate orange (BKTO). Fruit setting rates of these crosses were measured and the hybrids generated were planted in the field in 2008 and evaluated from 2010 to 2014, for the variables of plant mortality, visual vigor, plant height and trunk diameter. The descriptive statistics mean, variation range, coefficient of variation and Pearson skewness coefficient were calculated. Data were submitted to analysis of variance and the means of the treatments were grouped by the Scott-Knott test, both at 5 % significance. The progenies, having the ‘Sunki’ mandarin as the female parent, presented higher fruit setting rates and lower plant mortality rates than those obtained from the female parent ‘Rangpur’ lime, while zero plant mortality was observed in the SFM × BKTO cross. The crosses SCRL × SFM, SFM × BKTO, SFM × AGC and SFM × THOM have the potential to generate vigorous hybrids, resulting in rootstock varieties adapted to the landscape unit of Coastal Tableland.